주행중인 자동차 간의 공력 간섭현상 연구 - 이민준(Minjun Lee); 차두근(Dooguen Cha); 배희정(Heejung Bae); 권기현(Gihyun Kwan); 김지웅(Jiwoong Kim); 김문상(MoonSang Kim) (항공우주시스템공학회지, 2009)
Reduction of the aerodynamic drag is one of the most hot issues of car industries. Many researchers have studied in the area of drag reduction methodology using experimental tools or numerical tools. In general, car shape design is the main focus to reduce the drag in aerodynamic research area. However, not many people have studied the aerodynamic interference between running cars to figure out the drag variation. In this research, the aerodynamic interference between two running cars have been analyzed by using numerical tools, FLUENT 6.2. Several different models of cars and two different distances between two running cars are considered.